Analisis Pengaruh Perputaran Modal Kerja, Perputaran Kas, dan Perputaran Piutang terhadap Profitabilitas pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019–2021 - Anjelia, Anjelia (Jurnal KIAFE, 2024)
This study aims to examine the effects of working capital turnover, cash turnover, and receivables turnover on profitability in technology-sector companies listed on the Indonesia Stock Exchange during the 2019–2021 period. This study employs a quantitative approach using secondary data obtained from company financial statements. The sample was selected through purposive sampling and consisted of 17 companies. Data were analyzed using multiple linear regression with SPSS version 26. The results show that working capital turnover has no significant effect on profitability, cash turnover has a negative effect on profitability, and receivables turnover has a positive effect on profitability. The adjusted coefficient of determination is 38.6%, indicating that working capital turnover, cash turnover, and receivables turnover explain 38.6% of the variation in profitability, while the remaining 61.4% is explained by other factors outside the research model.